The Judicialization of Mega-Politics in Egypt’s Administrative Courts: Insight into The Rulings of the Egyptian State Council (2000-2020) - Bastawisy, Ahmed Kamal (AUC Knowledge Fountain, 2022)
The interrelationship between law, courts and politics has always been complex and multidimensional. The role and political significance of courts are prominent dimensions of this interrelationship. Over the past decades, there has been global expansion of judicial power, in parallel with the proliferation of modern constitutionalism principles. One of the fundamental manifestations of this trend is the judicialization of politics- the reliance on courts for addressing pivotal social, economic, moral and political controversies and public policy questions. This phenomenon manifests profound transfer of power from representative institutions, mainly legislatures and executives, to judiciaries. Political importance of courts expanded, in scope, to comprise “mega-politics”- the most crucial social, economic predicaments as well as controversies of utmost political prominence that influence the entire society. This research portrays the definitions and explanations of the judicialization of mega-politics globally. Then, analyzes judgments of the Egyptian State Council in the past two decades (2000-2020) to inspect the occurrence, forms and reasons of this phenomenon. The judicialization of pure politics is manifested in three forms, when courts: 1) Narrow the doctrine of sovereignty acts, that are immune of judicial review. 2) Perform explicit judicial law-making 3) Establish/abolish a major public policy. The phenomenon is attributed to institutional factors, mainly the constitutional framework that facilitates judicial activism, besides legal mobilization practiced by activists seeking for social change via strategic litigation. Furthermore, the main driving force behind the phenomenon is the judges’ professional perception of their role as guarantor of rights and liberties and a fundamental constitutional check on the executive authority. This perception is the result of accumulated progressive judicial practice- what I describe as “progressive judicial legacy.”